The politics of representation : modernism, feminism, postmodernism - Sonnet, Esther (1993)
This study is an investigation into the shifts in ways of knowing which have been subsumed under the label of postmodernism. More specifically, it is concerned to relate theories of Postmodernism to the construction of film as an object of knowledge and to feminism's place in a Modernist/postmodernist divide.